Nutraceuticals: Bridging Nutrition and Medicine for Future Wellness - Sarika L. Vikhe (Emerging Trends in Personalized Medicines, 2024)
Nutraceuticals are items that can be classified as food or a component of food and provide medical or health benefits. This paper discusses the concept of nutraceuticals, their classification, and their role in promoting health and wellness. As of 2023, the worldwide nutraceuticals market is expected to be valued at approximately USD 317.22 billion, indicating a high rate of increase. Growth is projected to reach USD 626.02 billion by 2029 at a compound annual growth rate (CAGR) of 5.09%. Nutraceuticals can be found in a variety of items, including herbal and natural remedies, functional foods, and pharmaceutical supplements. They are recognized for their role in disease treatment and prevention, anti-aging benefits, and cancer prevention. The paper highlights the various types of nutraceuticals, their health benefits, and the different dosage forms in which they are available. The paper also looks at the regulatory framework around nutraceuticals and the challenges the sector faces. The growing consumer interest in health-enhancing goods, advancements in research and development, and changing consumer lifestyles seem to be driving the promising future prospects for nutraceuticals
Keywords: Dietary supplements; Functional Foods; Health Benefits; Market; nutraceuticals